If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5 = x + -1(-1) Multiply -1 * -1 -5 = x + 1 Reorder the terms: -5 = 1 + x Solving -5 = 1 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -5 + -1x = 1 + x + -1x Combine like terms: x + -1x = 0 -5 + -1x = 1 + 0 -5 + -1x = 1 Add '5' to each side of the equation. -5 + 5 + -1x = 1 + 5 Combine like terms: -5 + 5 = 0 0 + -1x = 1 + 5 -1x = 1 + 5 Combine like terms: 1 + 5 = 6 -1x = 6 Divide each side by '-1'. x = -6 Simplifying x = -6
| t/5-3=7 | | 8x+3=6x+13 | | 81k-5=400 | | 2/9+2 | | 3a-5a+1=11 | | 4-5k=8+k | | 1/2x+x-9=180 | | -7=3t-15-t | | 87=3w | | 2x+6=19x | | 2x+(0)=5 | | p-7=-3+9p | | 3-x=2x-27 | | 10w-8=9+7w | | 2x+6x=18 | | 43y=301 | | 19x+27=103 | | 7x^2=16+x | | 4-3x=31 | | x-3=24 | | 7x-(3x-6)=38 | | 2x+5-3x=19x+2(25-10x) | | 5x-2y=22fory | | -2x^2+13x-3=0 | | 8x-3=12x-19 | | 12x-18=8x-6 | | ln(x)=1/7 | | 4z-0.7=5z | | v+2=-14-n | | 7-(5+a)/4 | | 11+(3x-7)=(6x+5)-3x | | m+18= |